Pengaruh Penggunaan Sosial Media dan E-Wom terhadap Keputusan Pembelian di Mediasi Kepercayaan (Studi pada Smartphone Xiaomi Daerah Istimewa Yogyakarta) - Sofyan Ilham Arohman; Muinah Fadhilah; Nonik Kusuma Ningrum (J-MAS (Jurnal Manajemen dan Sains), 2023)
The rapid development of the business world today causes companies to face intense competition. This research is classified as a type of quantitative research method, using a purposive technique. The results of the study are as follows. The use of social media has a positive effect on purchasing decisions for Xiaomi Smartphones with a p value of 0.031 < 0.05 1.65. E-wom has a positive effect on purchasing decisions for Xiaomi Smartphones with a p value of 0.033 < 0.05. The use of social media has a positive effect on trust with a p value of 0.015 <0.05. EWOM has a positive effect on trust with a p value of 0.030 <0.05. Trust has a positive and significant impact on purchasing decisions with a p value of 0.010 <0.05. Social media has a positive effect on purchasing decisions mediated by trust with a p value of 0.047 < 0.05. EWOM has no positive effect on purchasing decisions mediated by a p value of 0.096 > 0.05.